The Effect of Work Placement and Career Development on the Performance of Pt. Semen Baturaja (Persero) - Idris, M.; Agusria, Lesi; Mandela, Bobi Satria (Journal of Ecohumanism, 2024)
The purpose of this study is to determine and analyze the effect of Job Placement and Career Development on employee performance. The research approach that will be used in this study is a quantitative approach that is descriptive and associative. From the results of this study, it was found that there was an effect of work placement and career development on the performance of employees of PT Semen Baturaja (Persero) Tbk. The research object is all employees at PT Semen Baturaja (Persero) Tbk with a population of 912 employees, where the research sample is 90 people using proportionate stratified random sampling. The analysis technique in this study used multiple linear regression methods, hypothesis testing and coefficient of determination tests. Data processing using SPSS software version 25. From the results of the study showed that partially the job placement variable has a significant effect on employee performance. Partially, career development variables have no significant effect on employee performance. Simultaneously Work Placement and Development have a positive and significant effect on employee performance